Sistem Keamanan Kartu NFC Menggunakan Metode AES pada Sistem Pembayaran Elektronik - Bhaskoro, Susetyo Bagas; Anggraeni, Pipit; Nijam, E. Nashrul (Jurnal Sistem Cerdas, 2023)
To maintain data security, a method is needed that can improve data security, one of which is by using cryptographic techniques. In an effort to meet the needs of data security, cryptography focuses on understanding and applying techniques to protect messages. There are several methods used in cryptography, one of which is the AES method which is recognized as the best encryption algorithm for several reasons, such as using a sufficiently secure key, high processing speed, and ensuring data integrity and confidentiality. In this study, the AES method is used to secure data in the form of nominal balances stored on NFC cards. Based on the test results, it can be seen that the NFC card can function as a balance storage with a maximum limit of IDR 1,000,000. Then based on the confusion matrix method, the security system on the NFC card has an accuracy value of 81,81%, 83.3% precision, and 93,75% recall.